2019
DOI: 10.1097/md.0000000000017581
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of burnout syndrome among electrical and building technology undergraduate students in Nigeria

Abstract: Background:The investigation of burnout among undergraduate students is yet to receive the same amount of attention as burnout in employees. Despite the negative effects of burnout among students, there is dearth of literature on burnout problem among electrical and building technology undergraduate students. Therefore, this study aimed to determine the burnout levels and the effect of rational-emotive behavior therapy (REBT) on symptoms of burnout among electrical and building technology undergraduate student… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 36 publications
2
9
0
1
Order By: Relevance
“…In terms of REBT's effectiveness in assisting students in managing burnout, our present finding supports several studies which found similar results in student population. [3][4][5]11,12,14,23] Heber et al [26] show that internet-based intervention effectively reduced symptoms of stress. The finding of Harrer et al [27] supports online intervention delivery for reducing patient symptoms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In terms of REBT's effectiveness in assisting students in managing burnout, our present finding supports several studies which found similar results in student population. [3][4][5]11,12,14,23] Heber et al [26] show that internet-based intervention effectively reduced symptoms of stress. The finding of Harrer et al [27] supports online intervention delivery for reducing patient symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…In Nigerian studies of the university student population, internal consistency reliability tests show that Cronbach a score for the OLBI-S ranges from 0.77 to 0.90. [3][4][5]11,12,14,23] This online intervention was guided with an adapted electronic version of the manual of rational emotive behavioral therapy for the management of burnout [2] and was delivered using the telegram app. This online REBT intervention comprised cognitive restructuring strategies and re-education to alter students' burnout beliefs.…”
Section: Methodsmentioning
confidence: 99%
“…No ensaio clínico randomizado de Bakare et al (2019) foram avaliados 154 estudantes de graduação em tecnologia elétrica e predial de universidades públicas na zona sudeste da Nigéria, que tivessem a síndrome de Burnout. A intervenção consistiu em 10 semanas de tratamento psicológico realizadas durante um período de 4 meses.…”
Section: Duranteunclassified
“…Although indirect intervention influences the performance of students, especially in Science, Technology, Engineering, and Mathematics (STEM) degrees [41], proper intervention follows appropriate identification of the main causes of students being at risk. Prevalently, the following categories of indicators are insinuated in higher education; (a) low pre-entry marks [14], poor grade point average [17], muffled interview scores [18], (b) prior experience [17], prior acquaintance with the chosen programme and career goals [19], or prior intention to dropout [21], (c) dwindling performance in tests [17, 38], negative behaviour [21], extended exhaustion levels [19], the general extent of satisfaction with education [21], little effort exerted on tasks [21], poor study skills, as well as poor attendance [11] and participation in class [20]. Other factors that mildly feature when the topic of “at-risk” students is raised include lack of student support strategies [17] at institutional levels, students’ demographics [17], resource allocation [33, 38] at institutional levels, other educational barriers [13], emotional intelligence [34, 35], and learning behaviour [36, 37] of the student.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, a stop-out is a student who temporarily discontinues studies with the hope of re-registering at a later stage [9]. Contrary, burning-out is a situation where a student responds to chronic stress through emotional and physical exhaustion characterized by low productivity [14]. Then, failing is a situation where a student endures through a study programme, however, without achieving the desired performance to pass [9].…”
Section: Introductionmentioning
confidence: 99%